Border trade as a factor in the development of peripheral areas – the example of Poland’s eastern borderland - Malkowski, Arkadiusz (Handel przygraniczny jako czynnik rozwoju obszarów peryferyjnych na przykładzie pogranicza wschodniego Polski, 2019)
Changes in the functions of borders affect the socio-economic changes taking place in border regions. They had been hitherto treated as peripheral due to the low level of economic development. The increased permeability of borders has revived contacts between communities divided by borders. The article presents selected results of research conducted by the author in four provinces of the Polish eastern border region. The aim of the research was to determine the volume of border trade and its significance for peripheral regions. In the article, the available data from GUS [Main Statistical Office] and the Border Guard as well as the results of author’s own research based on CATI methodology were used. The conducted research indicates the importance of border trade for the development of Poland’s eastern border regions. The vast majority of foreigners visiting this area declare shopping as their main purpose of travel. The vast majority of Russians, Belorussians, and Ukrainians shop within fifty kilometers from the border. An important factor impacting on the volume of border traffic is the functioning of preferential agreements on low border traffic
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 75-85
Keywords: border trade; peripheral area; eastern borderland; handel przygraniczny; obszar peryferyjny; pogranicze wschodnie